Experiences of psychological mistreatment in older adults and promising practices: A scoping review protocol - Sabrina Lessard; Annie Bernatchez; Houda Garrach; Mélanie Couture; Claire Godard-Sebillotte; Sarita Israel; Rym Zakaria (PLoS ONE, 2025)
Objective This project aims to gain a thoroughly understanding of the characteristics and experiences of psychological mistreatment among older adults, acknowledging the diversity within this population. It also seeks to identify clinical tools and practices for its detection and intervention. While there is extensive literature on mistreatment of older adults, specific studies focusing on psychological aspects and intersecting social and identity dimensions are scarce. The findings will provide valuable insights for policymakers and healthcare professionals, helping to shape interventions and policies aimed at countering mistreatment in the ageing population. Introduction Psychological mistreatment involves a range of behaviors, expressions, and gestures—or the lack of appropriate actions—that negatively impact an individual's health and dignity. Often subtle and difficult to detect, this type of mistreatment is prevalent and can coexist with other types of abuse. Examination of psychological mistreatment, shaped by various social and identity dimensions, is lacking in current research, particularly regarding how it is experienced by older adults. This scoping review seeks to map the current knowledge on psychological mistreatment of older adults, while highlighting gaps and future directions for research. Inclusion criteria This scoping review will encompass studies that explore the characteristics and experiences of psychological mistreatment among older adults, including their experiences and those of perpetrators and witnesses. It will also identify clinical tools and practices for the detection and intervention of psychological mistreatment in this population. Method A scoping review will be undertaken by a multidisciplinary team, examining studies from post-2010, sourced from both bibliographic databases and grey literature, available in English or French. Employing an intersectional framework, the review will use Gender-Based Analysis Plus (GBA+) to examine how different forms of discrimination intersect and shape experiences of mistreatment. That is, this approach will help explore how social and identity dimensions—including gender, age, sexual orientation, ethnicity, socioeconomic status, and health conditions—shape the experiences and manifestations of psychological mistreatment.